The Influence of Novick Constructivism Learning Model on Critical Thinking Skills and Motivation in Online Learning - Arafa, Maretania; Dwiastuti, Sri; Fatmawati, Umi; Mahanani, Lina (Biosfer: Jurnal Tadris Biologi, 2021)
This study aims to determine the influence of the Novick constructivism learning model on 1) critical thinking skills and motivation, 2) the extent of influence of the Novick constructivism model on the aspects of critical thinking skills, 3) the extent of influence of the Novick constructivism model on learning motivation, and 4) the effectiveness of the model on critical thinking skills. The method used was quasi-experimental with a non-equivalent pretest-posttest control group design. The population was the tenth-grade science students. The critical thinking skills were assessed using a cognitive test, and the motivation was assessed using questionnaires. The MANOVA analysis was used to determine the model's influence. The regression analysis was used to determine the extent of the model's influence. The N-gain was used to determine the model's effectiveness. The MANOVA analysis obtained a significant value of 0.02, which was lower than 0. 05. Thus, H0 was rejected. The regression analysis showed the values of critical thinking skills ranged from high to low. The values consisted of strategies and tactics (46.49%), advance clarification (14.02%), basic support (13.96%), elementary clarification (13.62), and inference (11.88%). The motivation aspects ranging from high to low: relevance (26.35%), attention (25.98%), confidence (25.40%), and satisfaction (22.25%). The N-Gain score obtained by the experimental class was 0.437 in the moderate category. Based on the results, it can be concluded that 1) there was an influence of Novick constructivism model on critical thinking skills and motivation on online learning, 2) there was an unequal influence of the model on critical thinking aspects, and 3 ) motivation aspects, and 4) Novick constructivism model was relatively effective to be used in online learning.